Pediatric Chylo Lymphatic Mesentric Cyst: A Rare Entity - Binayke, Rachana Swapnil; Agale, Shubhangi V; Devi, Banasri; Gugaliya, Pinkesh; D’Costa, Grace F (Annals of Pathology and Laboratory Medicine, 2018)
Chylolymphatic cysts are rare variants of mesenteric lesions constituting 7.3% to 9.5% of all abdominal cysts displaying variable presentation and having surgical implications in the pediatric age group. The preoperative imaging studies are suggestive however histopathological examination remains the gold standard for diagnosis. A two months old male child was admitted with complaints of bilious vomiting for three days which was initially nonbilious in nature. There were no other significant medical or surgical complaints. X ray abdomen showed evidence of intestinal obstruction.Ultrasound revealed a large cystic lesion in abdominal cavity with internal echos arising from the ileal mesentery on ultrasonography. Subsequently exploratory laparotomy with excision of ileal segment involved by cyst and ileoileal anastomosis was performed and cyst was sent for histopathological examination. On syringing milky white fluid was aspirated which on biochemical analysis confirmed the chylous nature. The histopathological examination revealed an unilocular cyst having a fibrous wall infiltrated by lymphocytes and macrophages and lined by single layer of flattened epithelium with few dilated lymphatic channels consistent with chylolymphatic cyst. Although vary rare, chylomesenteric cyst should be kept as one of the differential diagnosis of cystic masses of the abdomen.